Implementasi Adiwiyata Dalam Literasi Ekologi Peserta Didik Di SMA Negeri 3 Palu - Nelwan, Satria Aditama; Novarita, Amalia (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
Adiwiyata and ecological literacy are very closely related and really support each other in order to achieve excellent environmental conditions to support the learning process at SMAN 3 Palu. This research aims to determine the implementation of adiwiyata in ecological literacy among students at SMAN 3 Palu. This type of research is a type of qualitative research, through a qualitative survey using observation, interviews and questionnaires based on the components of ecological literacy as indicators in this research including 1). Implication 2). Ecological Knowledge 3). Sociopolitical Knowledge 4). Knowledge of Environmental Problems 5). Cognitive Ability and 6). Responsible behavior towards the environment to explain how students understand the Adiwiyata program in ecological literacy at SMAN 3 Palu. The results of research on the implementation of Adiwiyata in ecological literacy among students at SMAN 3 Palu from the six indicators used as the basis for this research. Based on the research results, according to the data that has been obtained through an in-depth interview process and distribution of questionnaires to students as respondents, it is clear that the implementation of Adiwiyata in literacy Ecology for students at SMAN 3 Palu has been implemented well and correctly, where students have understood ecological literacy and applied the Adiwiyata programs that exist in the school environment.